2017
DOI: 10.1016/j.scitotenv.2016.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Acid rock drainage passive remediation: Potential use of alkaline clay, optimal mixing ratio and long-term impacts

Abstract: Acid rock drainage (ARD) is one of the most adverse environmental problems of the mining industry. Surface and ground water affected by this pollution are characterized by their acidity and the high content of sulfates and metals/metalloids. In this study, alkaline clay (AC), an industrial waste with a high alkalinity, which is utilized in the alumina refining process, was used as the remediation material to inhibit pyrite oxidation in waste coal piles. Through a series of laboratory experiments (static and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…Reactions R1, R2 and R3 reduce the pH and are characteristic of acid mine drainage processes (Banks et al, 1997;Robb, 1994) that produce well known adverse impacts on water resources (Plaza et al, 2017).…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Reactions R1, R2 and R3 reduce the pH and are characteristic of acid mine drainage processes (Banks et al, 1997;Robb, 1994) that produce well known adverse impacts on water resources (Plaza et al, 2017).…”
Section: Basic Conceptsmentioning
confidence: 99%
“…These acids act as solutes, causing leaching of metals from the waste and increasing the potential for subsequent water and soil contamination through dissolution and precipitation processes of secondary minerals [12][13][14][15][16]. Therefore, environmental management systems must be implemented to prevent and mitigate various environmental issues and improve the sustainability of both the mining industry and the communities living in mining areas.…”
Section: Introductionmentioning
confidence: 99%
“…In plot 2, the simulated SO 4 and Fe (total) captured the patterns of field observations as well, although the relative errors are 11% and over 100% for SO 4 and Fe (total), respectively. The much higher relative errors in plot 2 are due to the much lower concentrations in plot 2 than those in plot 1 except for the total calcium which might be caused by the dissolution of Ca carbonates, such as calcite (CaCO3), due to the alkaline additive, thus releasing Ca (Plaza et al, 2017). Usually, calcite is identified with acidic neutralization, enabling various metal removal mechanisms (Sun et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The compositions of 90% CR þ 10% BR, i.e., the amended zone in plot 2, mainly include Quartz, K-mica, Jarosite-K, Kaolinite, Dicalcium silicate, Sodalite, Calcite, Gehlenite, Gypsum, Hematite, Pyrite, Calcium aluminum sulfate, Calcium titanium oxide, Titanium dioxide and Gibbsite, which were detected in the mixing material sample and shown in Table 2c. Previous research has shown, based on the analyses of potential acidity production and acid neutralization, along with kinetic experiments, that a 10% BR/90%CR ratio will not potentially generate acid mine drainage and that this ratio is appropriate for long-term remediation (Plaza et al, 2017(Plaza et al, , 2018.…”
Section: Model Geochemcal Input Datamentioning
confidence: 99%